Konflik antara Perlindungan Rahasia Dagang dan Hak Pekerja dalam Klausul Non-Kompetisi - Wulan Purnamasari; Elza Syarief; Rina S. Shahrullah (SIGn Jurnal Hukum, 2023)
This study aims to scrutinize the Non-Competition Clauses in employment contracts as a manifestation of trade secrets and understand how these clauses impact an individual’s right to choose employment. This study uses normative legal research with the statute and comparative approaches. The collected legal material is then qualitatively analyzed to describe the problem and answer study purposes. The results show that including Non-Competition Clauses in employment contracts by employers is a strategic measure to protect trade secrets from competitors. However, every contract must fulfill the requirements for the agreement’s validity subjectively and objectively. Non-Competition Clauses can potentially conflict with workers’ rights as regulated in Article 28D section (2) of the 1945 Constitution, Article 38 section (2) of Law Number 39 of 1999, and Article 31 of Law Number 13 of 2003, thereby violating the objective requirements of employment contracts based on Article 52 section (1) point d of Law Number 13 of 2003. Therefore, it recommended that relevant parties review and evaluate the implementation of Non-Competition Clauses in employment contracts in Indonesia. Before incorporating this clause into the employment contract, employers must consider the agreement’s validity requirements and workers’ rights. Furthermore, the employment contract should further explain the definition and scope of the Non-Competition Clause to avoid different interpretations. Meanwhile, the Government is recommended to create clear regulations concerning the legitimacy of Non-Competition Clauses in employment contracts. These regulations must consider the balance between protecting trade secrets and workers’ rights to employment and income. Lastly, Courts should prioritize protecting workers’ rights in resolving disputes related to breaches of the Non-Competition Clause, especially if employers cannot prove the workers have violated the company’s trade secrets.